PENINGKATAN KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Eftiana, Fina (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
This study was motivated by the low mathematical literacy ability in mathematics learning. The purpose of this study was to determine the difference in the average improvement of students' mathematical literacy skills. The research method used quasi experimental with non-equivalent control group research design. The population in this study were all students at SMPN 51 Bandung grade VIII even semester of the 2022/2023 academic year. The samples in this study were class VIII.1 as the experimental class and class VIII.2 as the control class. In the experimental class learning using realistic mathematics education (RME) approach, while in the control class using deductive approach. The data collection technique used was a test. Based on the results of the analysis, it can be concluded that the average increase in students' mathematical literacy skills in learning flat-sided space building using the realistic mathematics education (RME) approach is in the high category has a significant difference compared to using the deductive approach in the medium category. It is recommended that research be carried out using more varied methods and media so that the results obtained are more optimal.